Variasi aktivator H2SO4 dan NaOH untuk pemurnian oli bekas dan emisi pengujian gas buang yang dihasilkan - Sasmita, A.; Reza, M.; Azzahra, N.W. (Universitas Mataram, 2024)
Oil consumption has increased every year in line with the increase in used oil produced. Used oil is included in the waste of Hazardous and Toxic Materials which have a bad impact on the environment. One of the technologies that can be utilized in processing used oil is refining because used oil contains base oil so that it can be reused as fuel. This study aimed to determine the best variation of using H2SO4 and NaOH in refining used oil, then the characteristics of the refined used fuel oil are tested for density, specific gravity, calorific value, viscosity, and moisture content, as well as exhaust emissions produced. The research method used was the acid and clay method with variations of H2SO4 and NaOH with the same values of 4% (P4), 5% (P5), and 6% (P6). The results showed that P6 type fuel is the best variation that comes closest to the diesel quality standard according to the Decree of the Directorate General of Oil and Gas 146 K/10/DJM/2020. In addition, the resulting emission also has the lowest value compared to the other two variations. The density values obtained were 857 kg/m3, a specific gravity of 0.857, a heating value of 47465 kJ/kg, a viscosity of 1.24 mm2/s, and a water content of 43.887 mg/kg. Meanwhile, in the exhaust emission testing, CO emissions were 0.030%, CO2 was 4.590%, HC was 19.50 ppm, and ƛ was 2.75.